1927 R.I. Pub. Laws 256, ch. 1052, §§ 1-2. - (:unkn) unknown (My University, 1927)
When used in this act the following words and phrases shall be construed as follows: "pistol" shall include any Pistol or revolver, and any shot gun, rifle or similar weapon with overall less than twenty-six inches, but shall not include any pistol without a magazine or any pistol or revolver designed for the use of blank cartridges only. "Machine gun" shall include any weapon which shoots automatically and any weapon which shoots more than twelve shots semi-automatically without reloading. "Firearm shall include any machine gun or pistol. . . "Crime of violence" shall mean and include nay of the following crimes or any attempt to commit any of the same, viz. murder, manslaughter, rape, mayhem, assault or battery involving grave bodily injury, robbery, burglary, and breaking and entering. "sell" shall include let or hire, give, lend and transfer, and the word "purchase" shall include hire, accept and borrow, and the expression "purchasing" shall be construed accordingly. § 2. If any person shall commit or attempt to commit a crime of violence when armed with or having available any firearm, he may in addition to the punishment provided for such crime of violence be punished as provided in this act. In the trial of a person for committing or attempting to commit a crime of violence the fact that he was armed with or had available a pistol without license to carry the same, or was armed with or had available a machine gun, shall be prima facie evidence of his intention to commit said crime of violence.
Keywords: COMMITTING CRIME W/ WEAPON; DEFINITIONS